Causality analysis of military expenditure, economic growth, and exchange rate in Indonesia 2000 – 2023 - Sa'bani, Shaghi Ratu; Iswati, Sri; Tumanggor, Muliahadi (Journal of Economics and Business Letters, 2025)
This study investigates the long-term relationship and causal dynamics among military expenditure, economic growth, and exchange rate in Indonesia over the period 2000-2023 to provide empirical insight into whether defense spending functions as a catalyst for economic growth or merely reflects the country’s fiscal capacity. Using annual time-series data from the World Bank’s World Development Indicators, the analysis applies the Johansen cointegration and Granger causality tests to assess both equilibrium and directional linkages. Before estimation, all variables are expressed in natural logarithms and subjected to the Augmented Dickey–Fuller test to ensure robustness of the empirical results. The findings confirm one significant cointegration relationship, indicating a stable long-term relationship among the variables. Granger causality results identify a unidirectional causality from economic growth to military expenditure, and from military expenditure to the exchange rate. These findings suggest that Indonesia’s defense spending is primarily responsive to fiscal capacity while influencing exchange-rate stability. The study contributes to the defense economic literature by integrating defense spending with economic development strategies through domestic procurement, fiscal efficiency, and the strengthening of strategic industries to maximize multiplier effects on economic growth and maintain macroeconomic stability.